The “hidden” Polish Influence in Italian Vocabulary: Not Only "Mazurka" and "Zloty" - Biasci, Gianluca (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
This essay aims to shed new light on the “hidden” contributions of the polish language and culture in the formation of Italian vocabulary. The survey involves both lexicographical repertoires and the language of the Internet, from which it is possible to draw terms that our dictionaries even ignore, such as polonismo and polacchismo. To the point of realizing that not even a very Italian, indeed very Neapolitan dessert, such as babà, is immune from the Polish linguistic (and gastronomic) contribution.